Rousseau y el contrato moral - Ibarra, Elina (2014)
Rousseau?s work talks to modernity, despite his resistance and distrust to extreme rationalism. In its way, Rousseau takes the issues raised by Machiavelli and La Boétie: political engineering and liberty. Rousseau is unhappy with the tendency to justify, in the name of order, the subjugation and exploitation of man. In The Social Contract he states the conditions for his model republic, which ensures happy freedom. Rousseau demonstrates how to obey orders without losing freedom. His task will be to show how it is possible to overcome the autonomy\nof certain spheres: combine politics and ethics, public and private, law and morality, putting political engineering in the service of morality. The formal character of the social contract operates as the moral foundation for political legitimization, thus turning the emerging republic in the best of all possible worlds. This is the core of the exercise of moral autonomy as opposed to the heteronomy suggested\nby rationalists political thinkers. And so, the distinction between morality and law is weakened, but leaves established the primacy of politics as key to understand the situation of men and as means for the attainment of freedom in a just order